MHV leaf amplitudes from parafermions - Laura Donnay; Gaston Giribet; Beniamino Valsesia (Journal of High Energy Physics, 2025)
Abstract We give a dual CFT representation of MHV leaf amplitudes in the large N and semiclassical limit in terms of non-compact parafermions and a single affine Kac-Moody current for SO(N). This representation is consistent with the other 2D CFT realization of 4D leaf amplitudes proposed in the literature, which is based on a dressed Liouville theory. The equivalence between the two CFT descriptions arises from the H 3 + $$ H_3^{+} $$ WZW-Liouville correspondence, applied to the SL(2, ℝ)/U(1) coset theory in the spectrally flowed sector.